DEVELOPMENT AND EVALUATION OF A COST-EFFECTIVE AERATION-FILTRATION SOLAR DISINFECTION SYSTEM FOR WATER TREATMENT (Nigerian Journal of Technology, 2025)
Solar disinfection (SODIS) of drinking water involves storing water in small transparent containers and exposing it to sunlight, but it has not yet gained widespread use despite being simple and low-cost. This study aimed to improve the acceptability of SODIS by developing and evaluating the effectiveness of a pilot-scale, semi-continuous flow, aeration-filtration SODIS (AF-SODIS) system that combines aeration, filtration, and solar disinfection in a single process. Over two weeks, the system was tested with feed water of 100 NTU turbidity and over 1.1 × 10⁵ MPN/100 mL of pathogens. The results showed that the system effectively removed over 97% of turbidity and 99.99% of E. coli. When compared to previously developed flow SODIS systems, this new system is more affordable and scalable, which could encourage greater adoption and sustained use. However, responses from potential users suggested that a substantial promotional and educational initiative would be required to establish SODIS treatment as a regular practice in rural areas of developing countries.